A History of Critical Thinking as an Educational Goal in Graduate Theological Schools - Florence, D. Christopher (Christian higher education, 2014)
The development of critical thinking skills among learners is a common educational goal across graduate theological schools. The purpose of this article is to provide a survey of some of the primary historical influences of the critical thinking movement in higher education in the United States and the movement's impact on graduate theological education. The author traces the roots of critical thinking beginning with Aristotle and follows the progression of development through Aquinas, Bacon, Descartes, Sumner, Ennis, and Brookfield. The contributions of the Protestant Reformation and the resulting development of higher education in colonial America are also explored. In addition, the article provides a brief review of recent research in the areas of effective pedagogy for and assessment of the development of critical thinking abilities in higher education in general, and in seminaries in particular.